Malaria surveillance system and Hospital Discharge Records: Assessing differences in Italy, 2011–2017 database analysis. Issue 48 (July 2022) - Dorrucci, Maria; Boccolini, Daniela; Bella, Antonino; Lucarelli, Claudia; D'Amato, Stefania; Caraglia, Anna; Maraglino, Francesco Paolo; Severini, Carlo; Gradoni, Luigi; Pezzotti, Patrizio
Abstract: Background: In Italy, surveillance through mandatory notification of cases to the National Surveillance System (NSS) has shown evidence of underreporting over the years. To evaluate the overall quality of malaria dataset, Hospital Discharge Records (HDRs) were analyzed as a second data source. Methods: Malaria cases by NSS and by HRDs were compared and analyzed from 2011-through 2017. The impact of cases was estimated by annual rates per 100, 000 residents. Results: Cases reported to NSS and to HDRs were 5, 149 and 6, 446, respectively. The annual rate recorded by NSS increased from 1.2 per 100, 000 in 2011 to 1.4 per 100, 000 in 2017, a similar trend was shown by HDRs, from 1.4 per 100, 000 in 2011 to 1.6 per 100, 000 in 2017. Every year, the number of NSS cases was lower than HDRs cases suggesting moderate underreporting of the mandatory notification. In both data sources adult males aged 25 to 44, and non-Italian travellers visiting friends and relatives were the most affected groups; Plasmodium falciparum was the prevalent agent identified, being the imported cases originated mainly from sub-Saharan Africa. As places of diagnosis and care, both data sources indicated hospitals located in Northern Italy in over 70% of cases. Conclusions: Although the comparison of malaria cases highlighted some underreporting by NSS, a fair agreement between the two institutional information systems was observed. The use of both data sources improves the performance of malaria surveillance in Italy, essentially for early warning systems in case of locally-acquired events and primary prevention in international travellers.